A manganese-based positive electrode material precursor, a preparation method and application thereof

CN117985771BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211340201.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2026-10-16
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

但由于Mn元素与NH3的络合能力较弱,Mn2+、Ni2+、Co2+三种金属离子特别容易与CO32-直接沉淀形成小颗粒,这样会出现两个技术难题:(1)开机粒度大,使得层状锰基正极材料空心化严重,振实密度偏低;(2)晶体生长过程中,部分新生成的颗粒不以原来晶种为基础继续生长,而是形成新相单独沉淀下来,导致一定比例的前驱体颗粒球形度差、振实密度偏低

Benefits of technology

[0048] Through the above technical solution, this disclosure employs a crystal nucleation and crystal growth isolation method. It synthesizes seed crystals with a specific medium particle size by adding a dispersant, a portion of a first solution containing a metal source, and a portion of a second solution containing a carbonic acid source. Then, by controlling the ratio of the amounts of the first solution added in the two additions, the sphericity, tap density, particle size, and distribution of the manganese-based cathode material precursor are controlled. The manganese-based cathode material precursor prepared by this disclosure exhibits good sphericity, high tap density, high particle size uniformity, and high relative crystallinity. The preparation process is simple and easy to implement, suitable for large-scale industrial production. The lithium-rich manganese-based cathode material prepared using this method exhibits excellent electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117985771B_ABST
    Figure CN117985771B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a manganese-based positive electrode material precursor, a preparation method and application thereof. The manganese-based positive electrode material precursor comprises particles of chemical formula Mn x Ni y Co z CO3; wherein x+y+z=1, 0.5≤x≤0.75, 0.1≤y≤0.25, and z>0; the tap density of the manganese-based positive electrode material precursor is 1.7 g / cm 3 above; the relative crystallinity of the manganese-based positive electrode material precursor is 80% or more; in the XRD pattern of the manganese-based positive electrode material precursor, the value of I (014) / I (018) is 2.5-4.0, I (014) represents the peak intensity of crystal face (014), and I (018) represents the peak intensity of crystal face (018). The tap density of the precursor prepared by the present disclosure is high, the sphericity is good, and the lithium-rich manganese-based positive electrode material prepared using the same has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of lithium-ion battery cathode material precursor preparation, specifically to a manganese-based cathode material precursor, its preparation method, and its application. Background Technology

[0002] Layered lithium-rich manganese-based cathode materials, such as xLi₂MnO₃·(1-x)LiMO₂ (M = at least one of Mn, Ni, and Co), can provide an actual discharge specific capacity of 250-290 mAh / g when the charging cutoff voltage is higher than 4.6V. They possess advantages such as high energy density, low raw material cost, and environmental friendliness, making them one of the important candidate cathode materials for developing high-energy-density (300Wh / kg) and low-cost lithium-ion batteries. However, layered lithium-rich manganese-based cathode materials also have disadvantages such as low volumetric energy density, rapid decay of specific capacity and median voltage, and poor rate performance. These disadvantages severely restrict the commercial application of layered manganese-based cathode materials.

[0003] The low volumetric energy density of layered lithium-rich manganese-based cathode materials is mainly due to poor internal particle density, severe hollowing, and poor sphericity of some secondary particles obtained by traditional preparation methods. Numerous studies have shown that the microstructure, tap density, particle size, and distribution of layered manganese-based cathode materials all depend on the properties of the precursor material. Layered manganese-based carbonate precursors (Mn...) 1-x-y Ni x Co y CO3 is a commonly used precursor material. To synthesize the aforementioned precursors, soluble metal salts of manganese, nickel, and cobalt (such as manganese-nickel-cobalt sulfates) and soluble carbonates are generally used as manganese-nickel-cobalt sources and precipitants. Ammonia-containing reagents (such as NH3·H2O and NH4HCO3) are used as complexing agents for the metal ions to control the crystallization precipitation rate and improve the sphericity and tap density of the precursor. However, because the complexing ability of Mn with NH3 is relatively weak, Mn... 2+ Ni 2+ Co 2+ Three metal ions are particularly prone to reacting with CO3. 2- Direct precipitation to form small particles presents two technical challenges: (1) The large particle size at startup leads to severe hollowing of the layered manganese-based cathode material and low tap density; (2) During crystal growth, some newly generated particles do not continue to grow based on the original seed crystal, but instead form a new phase that precipitates separately, resulting in a certain proportion of precursor particles having poor sphericity and low tap density. Summary of the Invention

[0004] The purpose of this disclosure is to provide a manganese-based cathode material precursor, its preparation method, and its application. The precursor has high tap density and good sphericity, and the lithium-rich manganese-based cathode material prepared using it has good electrochemical performance.

[0005] To achieve the above objectives, the first aspect of this disclosure provides a manganese-based cathode material precursor, characterized in that the manganese-based cathode material precursor contains a chemical formula of Mn. x Ni y Co z CO3 particles; where x + y + z = 1, 0.5 ≤ x ≤ 0.75, 0.1 ≤ y ≤ 0.25, z > 0;

[0006] The tap density of the manganese-based cathode material precursor is 1.7 g / cm³. 3 above;

[0007] The relative crystallinity of the manganese-based cathode material precursor is greater than 80%;

[0008] In the XRD pattern of the manganese-based cathode material precursor, I (014) / I (018) The value is 2.5-4.0, I (014) I represents the peak intensity of the crystal plane (014). (018) This represents the peak intensity of the crystal plane (018).

[0009] Optionally, the particle size distribution includes: D(min)≥3μm, D(0.1)≥5μm, D(0.5) is 9-13μm, and D(0.9)≤20μm.

[0010] Optionally, the particles include spherical particles and / or near-spherical particles;

[0011] Preferably, the number of spherical particles and quasi-spherical particles accounts for more than 98% of the total number of all particles.

[0012] A second aspect of this disclosure provides a method for preparing a manganese-based cathode material precursor, the method comprising the following steps:

[0013] (1) Prepare a first solution containing a metal source and a second solution containing a carbonic acid source, wherein the metal source includes a manganese source, a nickel source and a cobalt source;

[0014] (2) The dispersant, a portion of the first solution and a portion of the second solution are mixed and subjected to a first contact reaction to obtain seed crystals, wherein the D(0.5) of the seed crystals is below 3.0 μm; the time of the first contact reaction is 0.5-1 h;

[0015] (3) The seed crystal, another portion of the first solution, and another portion of the second solution are mixed to carry out a second contact reaction;

[0016] The volume ratio of the other portion of the first solution to the other portion of the first solution is 60:1 or higher.

[0017] Optionally, the D(0.5) of the seed crystal is below 2.2 μm.

[0018] Optionally, step (2) includes: adding a base liquid to the reaction vessel, and then adding a portion of the first solution and a portion of the second solution together to the reaction vessel to carry out the first contact reaction;

[0019] The dispersant includes sodium hexametaphosphate;

[0020] The bottom liquid accounts for 20%-40% of the volume of the reaction vessel;

[0021] The underlying solution is a 0.001-0.01 mol / L sodium hexametaphosphate solution;

[0022] The total volume of a portion of the first solution and a portion of the second solution accounts for 10%-20% of the volume fraction of the reactor.

[0023] A portion of the CO3 in the second solution 2- The molar ratio of the metal ions in a portion of the first solution to the metal ions in the first solution is (1.0-1.1):1;

[0024] The conditions for the first contact reaction include: a temperature of 25-65℃ and a stirring speed of 600-1000 r / min.

[0025] Optionally, step (3) includes: adding another portion of the first solution and another portion of the second solution together into the reaction vessel to carry out the second contact reaction; wherein the solution is added over a period of 60-150 hours.

[0026] When the volume of the material in the reactor exceeds 80% of the total volume of the reactor, the clear liquid is discharged from the reactor through a thickener, while the solid matter remains inside the reactor.

[0027] The other part of the second solution contains CO3 2- The molar ratio of metal ions in the first solution to those in the other part is (1.0-1.1):1;

[0028] The conditions for the second contact reaction include: a temperature of 25-65℃ and a stirring speed of 600-1000 r / min.

[0029] Optionally, the method further includes washing and drying the solid product obtained in step (3);

[0030] The drying conditions include: a temperature of 100-150℃ and a time of 5-20h.

[0031] Optionally, the manganese source includes one or more of manganese sulfate, manganese chloride, and manganese nitrate;

[0032] The nickel source includes one or more of nickel sulfate, nickel chloride, and nickel nitrate;

[0033] The cobalt source includes one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate;

[0034] The carbonic acid source includes carbonates, which include sodium carbonate and / or potassium carbonate.

[0035] Optionally, the concentration of metal ions in the first solution is 1.5-2.5 mol / L;

[0036] In the second solution, CO3 2- The concentration is 1.5-2.5 mol / L.

[0037] The third aspect of this disclosure provides a manganese-based cathode material precursor prepared using the method described in the second aspect of this disclosure.

[0038] This disclosure provides a fourth aspect of a method for preparing lithium-rich manganese-based cathode materials, the method comprising the following steps:

[0039] S1 mixes a lithium source with the manganese-based cathode material precursor described in the first or third aspect of this disclosure to obtain a first preproduct;

[0040] S2 involves heat-treating the first preproduct in an oxygen-containing atmosphere.

[0041] Optionally, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium nitrate;

[0042] The molar ratio of the lithium source (calculated as lithium element) to the manganese-based cathode material precursor (calculated as metal element) is (1.25-1.35):1;

[0043] Optionally, the mixing method is solid-phase ball milling, and the solid-phase ball milling time is 1-4 hours.

[0044] Optionally, in step S2, the heat treatment conditions include: a time of 10-20 hours and a temperature of 800-950°C.

[0045] The fifth aspect of this disclosure provides a lithium-rich manganese-based cathode material prepared using the method described in the fourth aspect of this disclosure.

[0046] Optionally, the tap density of the lithium-rich manganese-based cathode material is 1.9 g / cm³. 3 above.

[0047] The sixth aspect of this disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the lithium-rich manganese-based positive electrode material described in the fifth aspect of this disclosure.

[0048] Through the above technical solution, this disclosure employs a crystal nucleation and crystal growth isolation method. It synthesizes seed crystals with a specific medium particle size by adding a dispersant, a portion of a first solution containing a metal source, and a portion of a second solution containing a carbonic acid source. Then, by controlling the ratio of the amounts of the first solution added in the two additions, the sphericity, tap density, particle size, and distribution of the manganese-based cathode material precursor are controlled. The manganese-based cathode material precursor prepared by this disclosure exhibits good sphericity, high tap density, high particle size uniformity, and high relative crystallinity. The preparation process is simple and easy to implement, suitable for large-scale industrial production. The lithium-rich manganese-based cathode material prepared using this method exhibits excellent electrochemical performance.

[0049] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0050] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0051] Figure 1 The images show a comparison of scanning electron microscope (SEM) images of manganese-based cathode material precursors A1 and D1 prepared in Example 1 and Comparative Example 1 of this disclosure.

[0052] Figure 2 The particle size distribution curves are shown for the manganese-based cathode material precursors A1 and D1 prepared in Example 1 and Comparative Example 1 of this disclosure.

[0053] Figure 3 Comparison of X-ray diffraction (XRD) images of manganese-based cathode material precursors A1 and D1 prepared in Example 1 and Comparative Example 1 of this disclosure.

[0054] Figure 4 Comparison of scanning electron microscope (SEM) images of lithium-rich manganese-based cathode materials A1-1 and D1-1.

[0055] Figure 5 Comparison of X-ray diffraction (XRD) images of lithium-rich manganese-based cathode materials A1-1 and D1-1.

[0056] Figure 6 This is a comparison of the first charge-discharge curves of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1.

[0057] Figure 7This is a comparison chart of the cycle performance of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1.

[0058] Figure 8 This is a comparison chart of the rate performance of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1. Detailed Implementation

[0059] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0060] The first aspect of this disclosure provides a manganese-based cathode material precursor, the manganese-based cathode material precursor comprising the chemical formula Mn x Ni y Co z CO3 particles; where x + y + z = 1, 0.5 ≤ x ≤ 0.75, 0.1 ≤ y ≤ 0.25, z > 0;

[0061] The tap density of the manganese-based cathode material precursor is 1.7 g / cm³. 3 above;

[0062] The relative crystallinity of the manganese-based cathode material precursor is greater than 80%;

[0063] In the XRD pattern of the manganese-based cathode material precursor, I (014) / I (018) The value is 2.5-4.0, I (014) I represents the peak intensity of the crystal plane (014). (018) This represents the peak intensity of the crystal plane (018).

[0064] In this disclosure, the particles may contain trace impurities, which are not reflected in the chemical formula.

[0065] According to one embodiment of this disclosure, the particles include spherical particles and / or near-spherical particles. Preferably, the number of spherical particles and near-spherical particles accounts for more than 98% of the total number of all particles. The meaning of spherical and near-spherical is known in the art, for example, including particles with a sphericity of 0.8 or more, or, as observed by scanning electron microscopy (SEM), the ratio of the minimum distance to the maximum distance from the center of gravity of the particle to the particle surface is 0.7-1.

[0066] In this disclosure, the number of spherical and near-spherical particles accounts for more than 98% of the total number of particles, indicating that the manganese-based cathode material precursor of this disclosure has a high degree of sphericity, and the electrochemical performance of the lithium-rich manganese-based cathode material prepared using it is good.

[0067] According to one embodiment of this disclosure, the particle size distribution includes: D(min) ≥ 3 μm, D(0.1) ≥ 5 μm, D(0.5) ≥ 9-13 μm, and D(0.9) ≤ 20 μm; the particle size distribution is measured using a Malvern laser particle size analyzer. The manganese-based cathode material precursor synthesized by this method has a concentrated particle size distribution and high particle uniformity.

[0068] A second aspect of this disclosure provides a method for preparing a manganese-based cathode material precursor, the method comprising the following steps:

[0069] (1) Prepare a first solution containing a metal source and a second solution containing a carbonic acid source, wherein the metal source includes a manganese source, a nickel source and a cobalt source;

[0070] (2) The dispersant, a portion of the first solution and a portion of the second solution are mixed and subjected to a first contact reaction to obtain seed crystals, wherein the D(0.5) of the seed crystals is below 3.0 μm; the time of the first contact reaction is 0.5-1 h;

[0071] (3) The seed crystal, another portion of the first solution, and another portion of the second solution are mixed to carry out a second contact reaction;

[0072] The volume ratio of the other portion of the first solution to the other portion of the first solution is 60:1 or higher.

[0073] In this disclosure, the first solution containing the metal source does not contain any metal elements other than manganese, nickel and cobalt.

[0074] In this disclosure, a specific seed preparation time is used to generate seed crystals with a specific medium grain size, which is beneficial for preparing precursors with good sphericity and high tap density.

[0075] In this disclosure, no ammonium ions are introduced during the preparation of the manganese-based cathode material precursor; that is, neither the first solution nor the second solution contains ammonium ions.

[0076] According to one embodiment of this disclosure, the D(0.5) of the seed crystal is 2.2 μm or less. A suitable seed crystal size is advantageous for preparing a precursor with high tap density and for reducing the hollowness of the prepared lithium-rich manganese-based cathode material.

[0077] According to one embodiment of this disclosure, step (2) includes: adding a base liquid to a reaction vessel, and then adding a portion of the first solution and a portion of the second solution together to the reaction vessel to carry out a first contact reaction; the base liquid accounts for 20%-40% of the volume fraction of the reaction vessel; the total volume of a portion of the first solution and a portion of the second solution accounts for 10%-20% of the volume fraction of the reaction vessel, wherein the dispersant includes sodium hexametaphosphate, and the base liquid is a 0.001-0.01 mol / L sodium hexametaphosphate solution; the first contact reaction begins when the solution is first added to the reaction vessel, and ends after the solution is completely added, and the time from the beginning of the addition to the complete addition of the solution is the time of the first contact reaction.

[0078] According to one embodiment of this disclosure, a portion of the CO3 in the second solution 2- The molar ratio of the metal ions in the first solution to the metal ions in the first solution is (1.0-1.1):1, preferably (1.05-1.1):1.

[0079] According to one embodiment of this disclosure, the conditions for the first contact reaction include: a temperature of 25-65°C and a stirring speed of 600-1000 r / min.

[0080] According to one embodiment of this disclosure, step (3) includes: adding another portion of the first solution and another portion of the second solution together into the reactor to carry out the second contact reaction. The solution addition time is 60-150 hours, preferably 80-100 hours. The second contact reaction begins when the solution is first added to the reactor and ends after the solution is completely added. When the volume of the material in the reactor accounts for more than 80% of the total volume of the reactor, the clear liquid is discharged from the reactor through a thickener, and the precipitated solid remains in the reactor to continue crystal growth. In this method, by increasing the solid content of the slurry, the number of seed crystals is increased, the probability of secondary nucleation is reduced, thereby realizing synchronous nucleation and synchronous growth of crystals, extending the average residence time of the material, and improving the uniformity, sphericity, and relative crystallinity of the precursor particles.

[0081] According to one embodiment of this disclosure, in step (3), the CO3 in another portion of the second solution 2- The molar ratio of the metal ions in the first solution to the other part is (1.0-1.1):1, preferably (1.05-1.1):1.

[0082] According to one embodiment of this disclosure, the conditions for the second contact reaction include: a temperature of 25-65°C and a stirring speed of 600-1000 r / min.

[0083] According to one embodiment of this disclosure, the method further includes: performing solid-liquid separation on the mixture obtained in step (3), and then washing and drying the resulting solid product; wherein the solid-liquid separation method is conventional in the art, such as filtration; the washing is terminated when the filtrate is tested with barium chloride and no white precipitate appears; the drying conditions include: a temperature of 100-150°C and a time of 5-20 hours. The drying method is conventional in the art, such as drying in an oven.

[0084] According to one embodiment of this disclosure, the manganese source, nickel source, cobalt source, and carbonate source used are conventional in the art. The manganese source includes soluble manganese salts, preferably one or more of manganese sulfate, manganese chloride, and manganese nitrate; the nickel source includes soluble nickel salts, preferably one or more of nickel sulfate, nickel chloride, and nickel nitrate; the cobalt source includes soluble cobalt salts, preferably one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; and the carbonate source includes carbonates, such as sodium carbonate and / or potassium carbonate.

[0085] According to one embodiment of this disclosure, the total molar concentration of metal ions in the first solution is 1.5-2.5 mol / L, and the Mn in the first solution... 2+ Ni 2+ and Co 2+ The specific content is determined based on the ratio of Mn, Ni and Co in the manganese-based cathode material precursor.

[0086] According to one embodiment of this disclosure, in the second solution, CO3 2- The molar concentration is 1.5-2.5 mol / L.

[0087] The third aspect of this disclosure provides a manganese-based cathode material precursor prepared by the method described in the second aspect of this disclosure. This precursor has the same characteristics as the manganese-based cathode material precursor described in the first aspect of this disclosure, and will not be described in detail here.

[0088] This disclosure provides a fourth aspect of a method for preparing lithium-rich manganese-based cathode materials, the method comprising the following steps:

[0089] S1 mixes a lithium source with the manganese-based cathode material precursor described in the first or third aspect of this disclosure to obtain a first product;

[0090] S2 involves heat-treating the first preproduct in an oxygen-containing atmosphere.

[0091] According to one embodiment of this disclosure, the lithium source is conventional in the art, and may include one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate.

[0092] According to one embodiment of this disclosure, the molar ratio of lithium source (calculated as lithium element) to manganese-based cathode material precursor (calculated as metal element) is (1.25-1.35):1.

[0093] According to one embodiment of this disclosure, in step S1, the mixing method is solid-phase ball milling, and the time is 1-4 hours.

[0094] According to one embodiment of this disclosure, in step S2, the heat treatment conditions include: a time of 10-20 hours and a temperature of 800-950°C.

[0095] According to one embodiment of this disclosure, the oxygen-containing atmosphere is an air atmosphere or an oxygen atmosphere.

[0096] The fifth aspect of this disclosure provides a lithium-rich manganese-based cathode material prepared using the method described in the fourth aspect of this disclosure.

[0097] According to one embodiment of this disclosure, the lithium-rich manganese-based cathode material has the chemical formula Li. 1+δ Mn a Ni b Co c O2, where 0≤δ≤0.08, a+b+c=0.8, 0.4≤a≤0.6, 0.08≤b≤0.2, c>0. The chemical formula of the lithium-rich manganese-based cathode material described above does not consider the impurity content in the material, such as Na. + SO4 2- PO4 3- wait.

[0098] According to one embodiment of this disclosure, the tap density of the lithium-rich manganese-based cathode material is 1.9 g / cm³. 3 above.

[0099] The sixth aspect of this disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the lithium-rich manganese-based positive electrode material described in the fifth aspect of this disclosure.

[0100] In this disclosure, the types of negative electrode and electrolyte of lithium-ion battery are conventional in the art, and no specific requirements are made here, as long as they can achieve the solution of this disclosure.

[0101] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way.

[0102] All raw materials used in the examples were obtained through commercial purchases and, unless otherwise specified, were of analytical grade.

[0103] XRD testing conditions and instrument model: Philips X-ray powder diffractometer (USA). Test parameters: Cu target Kα light source, operating voltage 40kV, operating current 40mA, wavelength λ=0.154nm, scan rate 5° / min, scanning range 2θ=10-80°, step size 0.013°.

[0104] SEM testing conditions and instrument model: ZEISS Supra-55 from ZEISS GmbH, Germany; test parameters: voltage 5-20kV.

[0105] Test method and instrument model for tap density: BT-300, Dandong Better Instrument Co., Ltd.; 100g of the sample to be measured is placed in a 100mL graduated cylinder and vibrated 3000 times, with a vibration frequency of 300 times / min and an amplitude of 3mm.

[0106] Particle size testing instrument model: Mastersizer 2000, Malvern Ltd., UK; Test parameters: particle refractive index 1.52, particle absorption rate 0.1, dispersant is H2O, dispersant refractive index is 1.330, shading brightness is 5-10%, analysis mode is general.

[0107] Methods and instrument models for testing relative crystallinity: XRD was used to test the diffraction curve of pure-phase manganese carbonate at 2θ = 10⁻⁸°, and the integrated intensity of all diffraction peaks was defined as I₀; XRD was used to test the diffraction curve of the synthesized lithium-rich manganese-based precursor at 2θ = 10⁻⁸°, and the integrated intensity of all diffraction peaks was defined as I₀. c Relative crystallinity X c =I c / I0. Instrument model and test parameters: Philips X-ray powder diffractometer (USA). Test parameters: Cu target Kα light source, operating voltage 40kV, operating current 40mA, wavelength λ=0.154nm, scan rate 5° / min, scanning range 2θ=10-80°, step size 0.013°.

[0108] Example 1

[0109] The manganese-based cathode material precursor A1 was prepared using the following steps:

[0110] (1) According to the chemical formula Mn 0.68 Ni 0.16 Co 0.16 The molar ratio of manganese, nickel, and cobalt in CO3 was determined by adding manganese sulfate monohydrate, nickel sulfate hexahydrate, and cobalt sulfate heptahydrate to deionized water to prepare a first solution with a total molar concentration of metal ions of 2.0 mol / L.

[0111] Sodium carbonate was added to deionized water to prepare a second solution, CO3. 2-The molar concentration is 2.1 mol / L;

[0112] (2) Add 4L of deionized water to a 20L reactor and add 2.45g of sodium hexametaphosphate (NaPO3)6 to prepare a sodium hexametaphosphate aqueous solution with a molar concentration of 0.001mol / L as the base solution. At a stirring speed of 1000r / min and a reaction temperature of 40℃, add 1L of the first solution and 1L of the second solution in parallel and uniformly to the reactor to carry out the first contact reaction. The addition time is 0.5h. The resulting seed crystal is named CS-1.

[0113] (3) At a stirring speed of 1000 r / min and a reaction temperature of 40°C, 60 L of the first solution and 60 L of the second solution were added to the reactor in parallel and at a constant speed to carry out the second contact reaction. The addition time was 125 h. When the total volume of the slurry in the reactor reached 80% of the total volume of the reactor, the thickener was turned on to discharge the clear liquid out of the reactor. The precipitate remained in the reactor to continue crystal growth.

[0114] (4) After the feeding is complete, the mixture in the reactor is filtered and washed. The filtrate is tested with barium chloride. No white precipitate appears, so the washing is finished. Then the solid product is dried in an oven at 120°C for 10 hours and passed through a 200-mesh sieve to obtain the manganese-based cathode material precursor Al:Mn. 0.68 Ni 0.16 Co 0.16 CO3.

[0115] The morphology of the manganese-based cathode precursor A1 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 99% of the total number of particles.

[0116] The particle size distribution of seed crystal CS-1 was tested, and the test results are shown in Table 1.

[0117] The physicochemical parameters of the synthesized manganese-based cathode material precursor A1 were tested, and the test results are shown in Table 2.

[0118] Example 2

[0119] The manganese-based cathode material precursor A2 was prepared using the following steps:

[0120] (1) According to the chemical formula Mn 0.68 Ni 0.16 Co 0.16 The molar ratio of manganese, nickel, and cobalt in CO3 was determined by adding manganese sulfate monohydrate, nickel sulfate hexahydrate, and cobalt sulfate heptahydrate to deionized water to prepare a first solution with a total molar concentration of metal ions of 1.5 mol / L.

[0121] Sodium carbonate was added to deionized water to prepare a second solution, CO3. 2- The concentration was 1.65 mol / L;

[0122] (2) Add 8L of deionized water to a 20L reactor and add 9.78g of sodium hexametaphosphate (NaPO3)6 to prepare a sodium hexametaphosphate aqueous solution with a molar concentration of 0.002mol / L as the base solution. At a stirring speed of 1000r / min and a reaction temperature of 65℃, add 1.5L of the first solution and 1.5L of the second solution in parallel and at a uniform rate to the reactor for the first contact reaction. The addition time is 1h. The resulting seed crystal is named CS-2.

[0123] (3) At a stirring speed of 600 r / min and a reaction temperature of 65°C, 120 L of the first solution and 120 L of the second solution were added to the reactor in parallel and at a constant speed to carry out the second contact reaction. The addition time was 125 h. When the total volume of the slurry in the reactor reached 80% of the total volume of the reactor, the thickener was turned on to discharge the clear liquid out of the reactor. The precipitate remained in the reactor to continue crystal growth.

[0124] (4) After the feeding is complete, the mixture in the reactor is filtered and washed, and then the solid product is dried in an oven at 100°C for 20 hours and passed through a 200-mesh sieve to obtain the manganese-based cathode material precursor A2:Mn. 0.68 Ni 0.16 Co 0.16 CO3.

[0125] The morphology of the manganese-based cathode precursor A2 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 99% of the total number of particles.

[0126] The particle size distribution of seed crystal CS-2 was tested, and the test results are shown in Table 1.

[0127] The physicochemical parameters of the synthesized manganese-based cathode material precursor A2 were tested, and the test results are shown in Table 2.

[0128] Example 3

[0129] The manganese-based cathode material precursor A3 was prepared using the following steps:

[0130] (1) According to the chemical formula Mn 0.68 Ni 0.16 Co 0.16 The molar ratio of manganese, nickel, and cobalt in CO3 was determined by adding manganese chloride tetrahydrate, nickel chloride hexahydrate, and cobalt chloride hexahydrate to deionized water to prepare a first solution with a total molar concentration of metal ions of 2.5 mol / L.

[0131] Potassium carbonate was added to deionized water to prepare a second solution, CO3. 2- The molar concentration is 2.5 mol / L;

[0132] (2) 6 L of deionized water was added to a 20 L reactor, and 3.67 g of sodium hexametaphosphate (NaPO3)6 was added to prepare a sodium hexametaphosphate aqueous solution with a molar concentration of 0.001 mol / L as the base solution. At a stirring speed of 800 r / min and a reaction temperature of 25 °C, 1 L of the first solution and 1.05 L of the second solution were added to the reactor in parallel at a uniform rate to carry out the first contact reaction. The addition time was 0.5 h, and the resulting seed crystal was named CS-3.

[0133] (3) At a stirring speed of 800 r / min and a reaction temperature of 25°C, 70 L of the first solution and 73.5 L of the second solution were added to the reactor in parallel at a uniform speed to carry out the second contact reaction. The addition time was 150 h. When the total volume of the slurry in the reactor reached 80% of the total volume of the reactor, the thickener was turned on to discharge the clear liquid out of the reactor. The precipitate remained in the reactor to continue crystal growth.

[0134] (4) After the feeding is complete, the mixture in the reactor is filtered and washed, and then the solid product is dried in an oven at 150°C for 5 hours and passed through a 200-mesh sieve to obtain the manganese-based cathode material precursor A3:Mn. 0.68 Ni 0.16 Co 0.16 CO3.

[0135] The morphology of the manganese-based cathode precursor A3 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 99% of the total number of particles.

[0136] The particle size distribution of seed crystal CS-3 was tested, and the test results are shown in Table 1.

[0137] The physicochemical parameters of the synthesized manganese-based cathode material precursor A3 were tested, and the test results are shown in Table 2.

[0138] Example 4

[0139] The manganese-based cathode material precursor A4 was prepared using the following steps:

[0140] (1) According to the chemical formula Mn 0.5 Ni 0.25 Co 0.25 The molar ratio of manganese, nickel, and cobalt in CO3 was determined by adding manganese sulfate monohydrate, nickel sulfate hexahydrate, and cobalt sulfate heptahydrate to deionized water to prepare a first solution with a total molar concentration of metal ions of 2.0 mol / L.

[0141] Sodium carbonate was added to deionized water to prepare a second solution, CO3. 2- The concentration was 2.1 mol / L;

[0142] (2) Add 4L of deionized water to a 20L reactor and add 7.34g of sodium hexametaphosphate (NaPO3)6 to prepare a sodium hexametaphosphate aqueous solution with a molar concentration of 0.003mol / L as the base solution. At a stirring speed of 800r / min and a reaction temperature of 35℃, add 1L of the first solution and 1L of the second solution in parallel and uniformly to the reactor to carry out the first contact reaction. The addition time is 0.5h. The resulting seed crystal is named CS-4.

[0143] (3) At a stirring speed of 800 r / min and a reaction temperature of 25°C, 60 L of the first solution and 60 L of the second solution were added to the reactor in parallel and at a constant speed to carry out the second contact reaction. The addition time was 60 h. When the total volume of the slurry in the reactor reached 80% of the total volume of the reactor, the thickener was turned on to discharge the clear liquid out of the reactor. The precipitate remained in the reactor to continue crystal growth.

[0144] (4) After the feeding is complete, the mixture in the reactor is filtered and washed, and then the solid product is dried in an oven at 120°C for 10 hours and passed through a 200-mesh sieve to obtain the manganese-based cathode material precursor A4:Mn. 0.5 Ni 0.25 Co 0.25 CO3.

[0145] The morphology of the manganese-based cathode precursor A4 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 98.5% of the total number of particles.

[0146] The particle size distribution of seed crystal CS-4 was tested, and the test results are shown in Table 1.

[0147] The physicochemical parameters of the synthesized manganese-based cathode material precursor A4 were tested, and the test results are shown in Table 2.

[0148] Example 5

[0149] The manganese-based cathode material precursor A5 was prepared using the following steps:

[0150] (1) According to the chemical formula Mn 0.75 Ni 0.1 Co 0.15 The molar ratio of manganese, nickel, and cobalt in CO3 was determined by adding manganese sulfate monohydrate, nickel sulfate hexahydrate, and cobalt sulfate heptahydrate to deionized water to prepare a first solution with a total molar concentration of metal ions of 1.8 mol / L.

[0151] Potassium carbonate was added to deionized water to prepare a second solution; CO3 2- The concentration was 1.8 mol / L;

[0152] (2) 6 L of deionized water was added to a 20 L reactor, and 36.68 g of sodium hexametaphosphate (NaPO3)6 was added to prepare a sodium hexametaphosphate aqueous solution with a molar concentration of 0.01 mol / L as the base solution. At a stirring speed of 1000 r / min and a reaction temperature of 50 °C, 1.5 L of the first solution and 1.5 L of the second solution were added to the reactor in parallel at a uniform rate to carry out the first contact reaction. The addition time was 1 h, and the resulting seed crystal was named CS-5.

[0153] (3) At a stirring speed of 600 r / min and a reaction temperature of 50°C, 100 L of the first solution and 100 L of the second solution were added to the reactor in parallel and at a constant speed to carry out the second contact reaction. The addition time was 100 h. When the total volume of the slurry in the reactor reached 80% of the total volume of the reactor, the thickener was turned on to discharge the clear liquid out of the reactor. The precipitate remained in the reactor to continue crystal growth.

[0154] (4) After the feeding is completed, the slurry in the reactor is subjected to solid-liquid separation and washing. Then, the solid product is dried in an oven at 100°C for 20 hours and passed through a 200-mesh sieve to obtain the manganese-based cathode material precursor A5:Mn. 0.75 Ni 0.1 Co 0.15 CO3.

[0155] The morphology of the manganese-based cathode precursor A5 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 99.5% of the total number of particles.

[0156] The particle size distribution of seed crystal CS-5 was tested, and the test results are shown in Table 1.

[0157] The physicochemical parameters of the synthesized manganese-based cathode material precursor A5 were tested, and the test results are shown in Table 2.

[0158] Example 6

[0159] The manganese-based cathode material A6 was prepared using the method of Example 1, except that the addition time in step (3) was 100 h.

[0160] The morphology of the manganese-based cathode material precursor was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 99.5% of the total number of particles.

[0161] The particle size distribution of seed crystal CS-6 was tested, and the test results are shown in Table 1.

[0162] The physicochemical parameters of the synthesized manganese-based cathode material precursor A6 were tested, and the test results are shown in Table 2.

[0163] Comparative Example 1

[0164] The manganese-based cathode material precursor D1 was prepared using the method of Example 1, except that the volume ratio of the first solution in step (3) to the first solution in step (2) was 40:1, and the addition time in step (3) was 83h.

[0165] The morphology of the manganese-based cathode precursor D1 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 35% of the total number of particles.

[0166] The particle size distribution of seed crystal CS-D1 was tested, and the test results are shown in Table 1.

[0167] The physicochemical parameters of the synthesized manganese-based cathode material precursor D1 were tested, and the test results are shown in Table 2.

[0168] Comparative Example 2

[0169] The manganese-based cathode material precursor D2 was prepared using the method of Example 1, except that the substrate added in step (2) was deionized water and sodium hexametaphosphate (NaPO3)6 was not added.

[0170] The morphology of the manganese-based cathode precursor D2 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 85% of the total number of particles.

[0171] The particle size distribution of seed crystal CS-D2 was tested, and the test results are shown in Table 1.

[0172] The physicochemical parameters of the synthesized manganese-based cathode material precursor D2 were tested, and the test results are shown in Table 2.

[0173] Comparative Example 3

[0174] The manganese-based cathode material precursor D3 was prepared using the method of Example 1, except that the time for adding a portion of the first solution and a portion of the second solution in step (2) was 3 hours.

[0175] The morphology of the manganese-based cathode precursor D3 was measured by SEM and calculated. The number of spherical and near-spherical particles accounted for 35% of the total number of particles.

[0176] The particle size distribution of seed crystal CS-D3 was tested, and the test results are shown in Table 1.

[0177] The physicochemical parameters of the synthesized manganese-based cathode material precursor D3 were tested, and the test results are shown in Table 2.

[0178] Comparative Example 4

[0179] The manganese-based cathode material precursor D4 was prepared using the method in Example 1, except that the contact reaction time was adjusted to 3 hours.

[0180] The morphology of the manganese-based cathode precursor D4 was measured by SEM and calculated, and the number of spherical and near-spherical particles accounted for 80% of the total number of particles.

[0181] The particle size distribution of seed crystal CS-D4 was tested, and the test results are shown in Table 1.

[0182] The physicochemical parameters of the synthesized manganese-based cathode material precursor D4 were tested, and the test results are shown in Table 2.

[0183] Preparation Examples 1-6

[0184] The lithium-rich manganese-based cathode materials A1-1 to A6-1 were prepared using the following steps:

[0185] S1. Lithium carbonate and manganese-based cathode material precursor are ball-milled and mixed for 3 hours to obtain the first product.

[0186] S2. The first product was calcined at 900°C for 20 hours in air to obtain manganese-based cathode materials A1-1 to A6-1, the parameters of which are listed in Table 3.

[0187] The molar ratio of lithium source (calculated as lithium element) to manganese-based cathode material precursor (calculated as metal element) is 1.25:1.

[0188] Preparation of Comparative Examples 1-4

[0189] Lithium-rich manganese-based cathode materials D1-1 to D4-1 were prepared using the method of Preparation Example 1. The parameters are listed in Table 3. The difference is that the manganese-based cathode material precursors D1-D4 of Comparative Examples 1-4 were used as precursor materials.

[0190] SEM tests were performed on manganese-based cathode material precursors A1 and D1, and the results are as follows: Figure 1 As shown, the manganese-based cathode material precursor A1 prepared using the method disclosed herein exhibits very high sphericity. In contrast, the comparative sample D1, with insufficient crystal growth time, shows a large proportion of irregularly shaped particles and poor sphericity.

[0191] Particle size analysis was performed on manganese-based cathode material precursors A1 and D1, and the particle size distribution comparison curves are shown below. Figure 2As shown, it can be seen that when the ratio of the first solution in another part of step (3) to the first solution in a part of step (2) is small, the particle size of sample D1 is small.

[0192] XRD tests were performed on manganese-based cathode material precursors A1 and D1, and the results are as follows: Figure 3 As shown, the manganese-based cathode material precursor A1 prepared in this disclosure fully conforms to the crystal structure of manganese-based carbonate precursors and has no impurity peaks, indicating that the precursor material is a pure phase structure. Although the comparative sample D1 also has the crystal structure of manganese-based carbonate precursors, its diffraction peak intensity is lower, which means that its relative crystallinity is lower.

[0193] SEM tests were performed on lithium-rich manganese-based cathode materials A1-1 and D1-1, and the results are as follows: Figure 4 As shown, the lithium-rich manganese-based cathode material prepared using the manganese-based cathode material precursor disclosed herein has a very high sphericity.

[0194] XRD tests were performed on lithium-rich manganese-based cathode materials A1-1 and D1-1, and the results are as follows: Figure 5 As shown, according to Figure 5 It can be seen that the peak intensity of the diffraction peak of material A1-1 is significantly greater than that of sample D1-1, indicating that the crystal form of material A1-1 is more complete.

[0195] Test case

[0196] The lithium-ion batteries were prepared using the lithium-rich manganese-based cathode materials of the above-described preparation examples and comparative examples, following the steps below:

[0197] Accurately weigh the positive electrode material, conductive agent, and PVDF according to a mass ratio of 8:1:1. Add the three materials to NMP and stir to prepare a slurry. Coat the prepared slurry onto a 16μm thick aluminum foil and dry at 110℃ for 30 min. Roll the dried electrode sheet and punch it into an electrode sheet with a diameter of φ12 using a punching machine. Dry the electrode sheet in a vacuum oven at 120℃ for 12 h. The areal density of the electrode sheet is approximately 100 g / m³. 2 .

[0198] In an argon-atmospheric glove box, a CR2032 coin cell was assembled using a Li sheet as the negative electrode, the electrode sheet prepared above as the positive electrode, a 1 mol / L LiPF6 EC / EMC / DMC solution as the electrolyte, and a PP / PE polymer membrane.

[0199] Test conditions: charge / discharge voltage is 2.0-4.6V, charge / discharge rate is 0.1C, and test temperature is 25℃; during rate performance testing, the charging rate is 0.2C, and the discharging rates are 0.2C, 0.5C, 1C, 2C, and 3C.

[0200] The performance of the lithium-ion batteries prepared above was tested, and the results are listed in Table 3.

[0201] The comparison of the first charge-discharge curves of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1 is shown in the figure below. Figure 6 As shown.

[0202] The comparison of cycle performance of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1 is shown in the figure below. Figure 7 As shown.

[0203] The rate performance comparison chart of lithium-ion batteries using lithium-rich manganese-based cathode materials A1-1 and D1-1 is shown below. Figure 8 As shown.

[0204] Table 1

[0205] CS-1 0.884 1.737 3.362 CS-2 1.142 2.022 3.554 CS-3 1.076 1.996 3.477 CS-4 0.927 1.851 3.527 CS-5 1.150 2.197 4.311 CS-6 0.884 1.737 3.362 CS-D1 1.021 1.736 3.453 CS-D2 2.450 3.927 6.726 CS-D3 2.524 4.238 7.745 CS-D4 2.874 5.096 10.109

[0206] Table 2

[0207]

[0208] Table 3

[0209]

[0210]

[0211] According to the data in Table 2, the manganese-based precursor synthesized in this embodiment has higher tap density, narrower particle size distribution, and higher relative crystallinity. The electrochemical performance and tap density results of the manganese-based cathode material prepared using it are shown in Table 3. It can be seen from the data in the table that the lithium-rich manganese-based cathode material synthesized in this embodiment has higher tap density and better electrochemical performance.

[0212] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0213] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0214] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A manganese-based cathode material precursor, characterized in that, The manganese-based cathode material precursor contains chemical formula Mn x Ni y Co z CO3 particles; where x+y+z=1, 0.5≤x≤0.75, 0.1≤y≤0.25, z>0; The tap density of the manganese-based cathode material precursor is 1.7 g / cm³. 3 above; The relative crystallinity of the manganese-based cathode material precursor is above 80%; In the XRD pattern of the manganese-based cathode material precursor, I (014) / I (018) The value is 2.5-4.0, I (014) I represents the peak intensity of the crystal plane (014). (018) This represents the peak intensity of the crystal plane (018).

2. The manganese-based cathode material precursor according to claim 1, wherein, The particle size distribution includes: Dmin≥3μm, D10≥5μm, D50 is 9-13μm, and D90≤20μm.

3. The manganese-based cathode material precursor according to claim 1, wherein, The particles include spherical particles and / or near-spherical particles.

4. The manganese-based cathode material precursor according to claim 3, wherein, The number of spherical particles and quasi-spherical particles accounts for more than 98% of the total number of all particles.

5. A method for preparing the manganese-based cathode material precursor according to any one of claims 1-4, characterized in that, The method includes the following steps: (1) Prepare a first solution containing a metal source and a second solution containing a carbonic acid source, wherein the metal source includes a manganese source, a nickel source and a cobalt source; (2) The dispersant, a portion of the first solution and a portion of the second solution are mixed and subjected to a first contact reaction to obtain seed crystals, wherein the D50 of the seed crystals is below 3.0 μm; the time of the first contact reaction is 0.5-1 h. (3) The seed crystal, another portion of the first solution, and another portion of the second solution are mixed to carry out a second contact reaction; The volume ratio of the other portion of the first solution to the other portion of the first solution is 60:1 or higher.

6. The method according to claim 5, wherein, The D50 of the seed crystal is below 2.2 μm.

7. The method according to claim 5, wherein, Step (2) includes: adding a base liquid to the reactor, and then adding a portion of the first solution and a portion of the second solution together to the reactor to carry out the first contact reaction; The dispersant includes sodium hexametaphosphate; The bottom liquid accounts for 20%-40% of the volume of the reaction vessel; The underlying solution is a 0.001-0.01 mol / L sodium hexametaphosphate solution; The total volume of a portion of the first solution and a portion of the second solution accounts for 10%-20% of the volume fraction of the reactor. A portion of the CO3 in the second solution 2- The molar ratio of the metal ions in a portion of the first solution to the metal ions in the first solution is (1.0-1.1):1; The conditions for the first contact reaction include: a temperature of 25-65℃ and a stirring speed of 600-1000 r / min.

8. The method according to claim 7, wherein, Step (3) includes: adding another portion of the first solution and another portion of the second solution together into the reaction vessel to carry out the second contact reaction; wherein the solution is added over a period of 60-150 hours. When the volume of the material in the reactor exceeds 80% of the total volume of the reactor, the clear liquid is discharged from the reactor through a thickener, while the solid matter remains inside the reactor. The other part of the second solution contains CO3 2- The molar ratio of metal ions in the first solution to those in the other part is (1.0-1.1):1; The conditions for the second contact reaction include: a temperature of 25-65℃ and a stirring speed of 600-1000 r / min.

9. The method according to claim 5, wherein, The method further includes washing and drying the solid product obtained in step (3); The drying conditions include: a temperature of 100-150℃ and a time of 5-20h.

10. The method according to claim 5, wherein, The manganese source includes one or more of manganese sulfate, manganese chloride, and manganese nitrate; The nickel source includes one or more of nickel sulfate, nickel chloride, and nickel nitrate; The cobalt source includes one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; The carbonic acid source includes carbonates, which include sodium carbonate and / or potassium carbonate.

11. The method according to claim 5, wherein, In the first solution, the concentration of metal ions is 1.5-2.5 mol / L; In the second solution, CO3 2- The concentration is 1.5-2.5 mol / L.

12. A method for preparing lithium-rich manganese-based cathode materials, characterized in that, The method includes: S1. Mix the lithium source with the manganese-based cathode material precursor according to any one of claims 1-4 to obtain the first preproduct; S2 The first preproduct is heat-treated in an oxygen-containing atmosphere.

13. The method according to claim 12, wherein, The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate, and lithium nitrate. The molar ratio of the lithium source (calculated as lithium element) to the manganese-based cathode material precursor (calculated as metal element) is (1.25-1.35):

1.

14. The method according to claim 12, wherein, The mixing method is solid-phase ball milling, and the solid-phase ball milling time is 1-4 hours.

15. The method according to claim 12, wherein, In step S2, the heat treatment conditions include: a time of 10-20 hours and a temperature of 800-950°C.

16. A lithium-rich manganese-based cathode material prepared by the method according to any one of claims 12-15.

17. The lithium-rich manganese-based cathode material according to claim 16, wherein, The tap density of the lithium-rich manganese-based cathode material is 1.9 g / cm³. 3 above.

18. A lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte, and a negative electrode, characterized in that, The cathode comprises the lithium-rich manganese-based cathode material as described in claim 16 or 17.

Citation Information

Patent Citations

  • Manganese-rich carbonate precursor with high sphericity degree as well as preparation method and application of manganese-rich carbonate precursor

    CN114195204A